2018
DOI: 10.1177/0734016817753266
|View full text |Cite
|
Sign up to set email alerts
|

Social Control Versus Social Learning: Self-Efficacy for Future Academic Success and Peer Delinquency as Mediators of the Parental Support–Delinquency Relationship

Abstract: The purpose of this study was to determine whether low self-efficacy for future academic success and peer delinquency mediated the relationship between weak parental support and delinquency, and if so, establish the order of mediation. Members of the Flint (Michigan) Adolescent Study ( N = 850) served as participants in this study, which compared a pathway based on social control principles (weak parental support → low self-efficacy → peer delinquency → participant delinquency) with a pathway based on social l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(67 reference statements)
1
4
0
Order By: Relevance
“…By internalizing the external social context, in this case, parental support, and acting on this symbolized interpretation of the social environment, the child, in effect, reduced their own chances of engaging in future delinquent behavior. These results are consistent with prior studies showing that internalized processes like cognitive distortions (de Vries et al, 2016), moral disengagement (Ishoy, 2017), and weak academic selfefficacy (Walters, 2019) are capable of mediating the parental support-delinquency relationship. More recently, Walters et al (2022) discovered that perceived parental competence suppressed future delinquency by increasing cognitive control and moral cognition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By internalizing the external social context, in this case, parental support, and acting on this symbolized interpretation of the social environment, the child, in effect, reduced their own chances of engaging in future delinquent behavior. These results are consistent with prior studies showing that internalized processes like cognitive distortions (de Vries et al, 2016), moral disengagement (Ishoy, 2017), and weak academic selfefficacy (Walters, 2019) are capable of mediating the parental support-delinquency relationship. More recently, Walters et al (2022) discovered that perceived parental competence suppressed future delinquency by increasing cognitive control and moral cognition.…”
Section: Discussionsupporting
confidence: 92%
“…Second, neither study tested the total indirect effect with bootstrapped confidence intervals, the current standard for research in mediation analysis (Hayes, 2022). In a pair of studies that used at least three waves of data and tested the total indirect effect with bootstrapped confidence intervals, low self-efficacy for academic success/peer delinquency (Walters, 2019) and peer delinquency/gang affiliation (Walters, 2020b) were found to mediate the relationship between low parental support and child delinquency.…”
Section: Identifying a Mechanism For The Parenting-delinquency Relati...mentioning
confidence: 99%
“…Social learning theory is an important scheme for exploring the process of human cognition formation [ 47 ]. According to this theory, driven by goals, individuals will form relevant expectations and action plans in combination with the evaluation of themselves and the environment, and then constantly reflect on themselves in the process of action to form the evaluation of self-efficacy, which will ultimately affect their expectations of themselves and their behavior.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…First, self-efficacy refers to an individual’s speculation and judgment on whether they can complete a certain behavior [ 50 ]. According to social learning theory, people’s sense of self-efficacy often comes from their past social experiences [ 47 ]. For example, independently completing a certain task and achieving success can bring people a satisfactory experience and arouse their ambition to continuously participate and continuously improve this task [ 50 ].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…One study found that 70.5% of youth were influenced by peer pressure to commit a delinquent act (Lobos, 2020). Research has also found that boys are often more sensitive to negative peer effects than girls (Augustyn & McGloin, 2013; Piquero et al, 2005; Walters, 2019), while girls tend to be impacted more by family influences, both positive and negative, as compared to boys (Silverman & Caldwell, 2005; Walters, 2013; Walters, 2019). While evaluating parental control/support and peer deviance as predictors of participant delinquency, Bowman and colleagues (2007) discovered that parental control and support predicted delinquency in girls but not boys and peer deviance predicted delinquency in boys but not girls.…”
Section: Adverse Childhood Experiences (Aces)mentioning
confidence: 99%